2021
DOI: 10.2991/assehr.k.210424.075
|View full text |Cite
|
Sign up to set email alerts
|

The Requirement of Business Model in Commercialization Research Products of Higher Education Institutions (HEIS):

Abstract: This paper describes a business model (BM) requirement for research product commercialization within Indonesia HEIs. The objective is to determine the importance of BM as an assessment for research product commercialization feasibility. The study is conducted using a qualitative approach in selected 21 tertiary institutions in Indonesia comprised of nine universities and twelve polytechnics. Interviews and FGDs are carried out by involving the heads of related units for the commercialization process and senior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…These elements of competencies provide a blueprint for businesses to follow, which if implemented correctly, significantly reduces the risk of contamination and ensures easier maintenance and sanitation processes. Lasambouw et al, (2015) found that the element of competence is associated with a step-by-step procedure in the research cycle conducted by lecturers. Each unit of competency is broken down into specific tasks to be performed, which facilitates tracking and appraisal of research performance.…”
Section: Traceability Of Element Of Competency To Step-by-step Proced...mentioning
confidence: 98%
See 1 more Smart Citation
“…These elements of competencies provide a blueprint for businesses to follow, which if implemented correctly, significantly reduces the risk of contamination and ensures easier maintenance and sanitation processes. Lasambouw et al, (2015) found that the element of competence is associated with a step-by-step procedure in the research cycle conducted by lecturers. Each unit of competency is broken down into specific tasks to be performed, which facilitates tracking and appraisal of research performance.…”
Section: Traceability Of Element Of Competency To Step-by-step Proced...mentioning
confidence: 98%
“…Additionally, the traceability of these standards in different cultural and operational settings within the food industry warrants further investigation. Lasambouw et al, (2015) found that the development of assessment models is directed to measure the gap between the competencies possessed by lecturers and established competency standards, reflecting the importance of tracking performance criteria to actual work instructions in the workplace. Furthermore, Malitano & Chibomba, (2019) demonstrate how a well-integrated appraisal system with work instructions can improve transparency, efficiency, and effectiveness in performance management in the workplace.…”
Section: Traceability Of Performance Criteria To Work Instructions In...mentioning
confidence: 99%